"Pan Sędzia Deluty. Sceny z pierwszych lat panowania Stanisława Augusta" (edycja nieznanego rękopisu) = Snippets. The thing about the abandoned text of a novel entitled "Judge Deluty. Scenes from the First Years of Stanisław August Reign" by Adam Jerzy Czartoryski (an issue of unknown manuscript) - Grabias-Banaszewska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Adam Jerzy Czartoryski's novel entitled [Mister] "Judge Deluty" [Pan sędzia Deluty] was first ever published in 2005 on the base of the text's handwriting copy made by Leonard Niedźwiecki, Czartoryski's secretary. However, the autograph is much richer. The content of its first nine cards Czartoryski named them "snippets" are in connection with the novel despite the fact that they appear to be only a secondary text.
Keywords: powieść; edytorstwo; autograf; rękopis; Czartoryski, Adam Jerzy (1770-1861); novel; editorship; autograph; manuscript